2002
DOI: 10.1530/eje.0.1470461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-lasting raloxifene treatment on serum prolactin and gonadotropin levels in postmenopausal women

Abstract: Objective: To evaluate the effects of a 6 month administration of raloxifene hydrochloride, a selective estrogen receptor modulator which was recently approved for the prevention of osteoporosis, on serum gonadotropin and prolactin (PRL) levels and on TRH-stimulated PRL responsiveness in postmenopausal women who have not undergone estrogen replacement therapy. Design and methods: Sixteen healthy postmenopausal women were divided into two groups on the basis of their bone status, evaluated by dual energy X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Further studies are underway to establish the contribution of PRL to this phenotype. Indeed, a role for PRL is supported by the findings of Aoki Mdel et al [64], who recently demonstrated that TAM induces apoptosis in lactotrophs, while a separate study showed that administration of the antiestrogen, raloxifene, to postmenopausal women suppressed levels of serum PRL [65]. Taken together, these findings suggest that higher doses of TAM may restrict mammary development through a negative impact on pituitary cell number or function.…”
Section: Discussionmentioning
confidence: 79%
“…Further studies are underway to establish the contribution of PRL to this phenotype. Indeed, a role for PRL is supported by the findings of Aoki Mdel et al [64], who recently demonstrated that TAM induces apoptosis in lactotrophs, while a separate study showed that administration of the antiestrogen, raloxifene, to postmenopausal women suppressed levels of serum PRL [65]. Taken together, these findings suggest that higher doses of TAM may restrict mammary development through a negative impact on pituitary cell number or function.…”
Section: Discussionmentioning
confidence: 79%
“…2 Serum levels (mean ± SEM) of FSH and LH in experiments (Exp) in which oestrogen-deprived postmenopausal women were treated with (a) raloxifene (R) or clomiphene (Cl) plus E2 (Group 1, n = 8), or (b) E2 plus R or Cl (Group 2, n = 8). In particular, in postmenopausal women, raloxifene at the dose of 120 mg /day for 1 week had no significant effects on basal gonadotrophin levels (Malacara et al, 2001), while at 60 mg /day raloxifene induced a significant decrease in basal FSH values at 3 months (Reindollar et al, 2002) or no change in FSH and LH values at 3 and 6 months (Lasco et al, 2002). *P < 0·05, **P < 0·01, ***P < 0·001 (difference from D0), +P < 0·05 (difference from D20).…”
Section: Discussionmentioning
confidence: 89%
“…In terms of hormonal secretion, clomiphene in oestrogen-deprived postmenopausal women demonstrates mainly oestrogenic activities suppressing basal and GnRH-induced gonadotrophin secretion, an effect that can be reversed by oestrogen pretreatment (Hashimoto et al ., 1976a;Messinis & Templeton, 1990). Little is known about the effects of this agent on basal gonadotrophin secretion because data are limited and conflicting (Baker et al ., 1998;Lasco et al ., 2002;Reindollar et al ., 2002). Little is known about the effects of this agent on basal gonadotrophin secretion because data are limited and conflicting (Baker et al ., 1998;Lasco et al ., 2002;Reindollar et al ., 2002).…”
mentioning
confidence: 99%
“…High prolactin levels have been associated with osteopenia, decreased bone density, and increased osteoporosis risk, possibly as a result of a reduction in estrogen levels [40, 41]. In addition, long-term administration of raloxifene, which has been shown to decrease fracture risk in postmenopausal women with osteoporosis, decreases serum prolactin levels [42]. …”
Section: Discussionmentioning
confidence: 99%